Meat quality in autochthonous Mediterranean pig breeds reared in organic production systems - Karatosidi, Despoina; Symeon, Georgios; Michailidis, Georgios; Avgeris, Efthymios; Tarricone, Simona; Giannico, Francesco; Colonna, Maria Antonietta (Frontiers in Animal Science, 2025)
Black pig breeds are autochthonous populations present in many Mediterranean countries, reared on sustainable production systems as they can exploit the feed resources available on the territory. While in Italy the black pig breeds have been thoroughly studied, in Greece there is still lack of information about the productive performances of this animal. This is a comparative study aiming at investigating on the carcass traits and meat quality features of the autochthonous Greek Black Pig and Italian Apulo-Calabrese black pig reared under organic production systems, typical of the rural areas of the two countries, on the quality parameters, chemical composition and fatty acid profile of the Longissisum lumborum muscle. A total of 40 pigs were used, 20 for each genotype, within each genotype two sub-groups were made and slaughtered at 9 or 12 months of age, respectively. When slaughtered at 12 months of age, meat from the Greek pig was brighter and more tender than the Apulo-Calabrese, while the chemical composition from the Italian breed showed a lower protein and intramuscular fat content than the Greek one. A higher percentage of Saturated Fatty Acids (SFA), total n-3 and n-6 fatty acids in turn of a lower amount of Mono Unsaturated Fatty Acids (MUFA) was found in meat from both the Greek groups. This trial may be considered as a first step to evaluate meat characteristics of the autochthonous Greek black pig and, therefore, a tool to increase awareness of this local genotype and its exploitation.